Digital innovations in poetry: Practices of creative writing faculty in online literary publishing. (27th April 2015) - Fleming‐May, Rachel A.; Green, Harriett
Abstract : This research project explores, through a series of online surveys and subsequent series of individual interviews, stakeholders' attitudes and practices regarding poetry published exclusively in web‐based media. This article specifically examines the project's gathered data on creative writing faculty from North American institutions who were surveyed and interviewed about online poetry publishing as both creators and consumers of the literary works. This study also explores creative writing faculty members' opinions about publishing in online literary publications in regard to career impact, including tenure and promotion. As online literary publishing disrupts what continues to be a very print‐oriented practice, Rogers' "diffusion of innovations" provides a useful framework for exploring these issues. Because this project considers how innovations diffuse throughout a specific group of artists and scholars, and the information needs that emerge from these transformations, the concept of "communities of practice" also informed data analysis.